Student and Preceptor Experiences in a Mini Longitudinal Integrated Clerkship: A Participatory Self-Study - Paulus, Ryan (PRiMER, 2020)
INTRODUCTION: Students participating in longitudinal integrated clerkships (LIC) experience longitudinal, comprehensive care of patients, report improved satisfaction with their training, and express increased interest in pursuing a career in primary care. To gain these benefits without requiring major curricular change, Ohio University Heritage College of Osteopathic Medicine created a year-long mini LIC (mLIC). As participants in the mLIC, we sought to measure our own experiences, gathering data in a systematic way to share our perceptions. METHODS: We developed an online survey that included scale and open-ended questions. Eight students and three cooperating preceptors completed the survey. We analyzed short answer responses thematically; we analyzed multiple choice responses using descriptive statistics. RESULTS: Participants reported increased interest in underserved rural primary care. Students described the continuity with patients as the most beneficial aspect. Students felt the increased autonomy, self-learning, and hands-on nature of the mLIC increased clinical confidence and preparedness for intern year. Students stated the mLIC provided learning opportunities they would not have experienced in traditional block-based clerkships, including longitudinal relationships and prolonged exposure to primary care. Preceptors stated they were able to learn new ideas from the students and were surprised by how much they benefited from the experience. CONCLUSION: Students did experience many of the benefits of a traditional LIC in our mLIC format focused on a longitudinal experience in family medicine. Students and preceptors were positively impacted and felt the mLIC led to increased student learning, professional development, and increased preceptor satisfaction. Our conclusions are limited by the small sample size included in our study.